Agricultural insect hybridization and implications for pest management. Issue 11 (14th June 2019) - Corrêa, Alberto S; Cordeiro, Erick MG; Omoto, Celso
ABSTRACT: Biological invasions, the expansion of agricultural frontiers, and climate change favor encounters of divergent lineages of animals and plants, increasing the likelihood of hybridization. However, hybridization of insect species and its consequences for agroecosystems have not received sufficient attention. Gene exchange between distinct and distant genetic pools can improve the survival and reproduction of insect pests, and threaten beneficial insects in disturbed agricultural environments. Hybridization may be the underlying explanation for the recurrent pest outbreaks and control failures in putative hybrid zones, as suspected for bollworm, corn borer, whiteflies, and stink bugs. Reliable predictions of the types of changes that can be expected in pest insect genomes and fitness, and of their impacts on the fate of species and populations remain elusive. Typical steps in pest management, such as insect identification, pest monitoring, and control are likely affected by gene flow and adaptive introgression mediated by hybridization, and we do not have ways to respond to or mitigate the problem. To address the adverse effects of farming intensification and global trade, we must ensure that current integrated pest management programs incorporate up‐to‐date monitoring and diagnostic tools. The rapid identification of hybrids, quantification of levels of introgression, and in‐depth knowledge of what genes have been transferred may help to explain and predict insect population outbreaks and control failures in the future. © 2019 Society of Chemical Industry Abstract : Hybridization constitutes a severe concern for pest management worldwide. Here, we outline possible scenarios for hybridizations in crop fields, discussing how this can affect the management of economically important species and how we can mitigate the negative impacts.